Immediate-use steam sterilization and the effect on surgical site infection risk in an acute care facility - Victoria D. Crall; Casey L. Lewis; Avisha Risnear; Jason Miller; Joanne Sherer; Ashley M. Ayres; Graham M. Snyder (Cambridge University Press, 2024)
Immediate-use steam sterilization (IUSS) shortens the time of sterilization but may increase the risk of surgical site infection (SSI). Among 23,919 procedures with 416 (1.7%) procedures resulting in SSI, IUSS was associated with a 1.52 (95% CI, 1.10-2.11) times higher risk of SSI. IUSS should be minimized.